Stabilize the structureair-nuts semi products surfactants - Товма, Лідія Федорівна; Горальчук, Андрій Богданович; Гринченко, Ольга Олексіївна (Eastern-European Journal of Enterprise Technologies, 2014)
The study of foaming capacity and stability of the foam, based on egg-white in the presence of fat have shown that fat is the antifoaming agent and leads to the foam destruction. Experimental investigations of the egg-white effect on foaming capacity and foam stability in the presence of fat, surfactants (GMS, LACTEM, lecithin’s, DATEM, SSL) with different NLB values are presented in the paper. The influence regularities of the surfactant concentration on foaming capacity and foam stability of systems, based on egg-white in the presence of fat were first defined in the paper. It was established that the surfactant concentration determines foaming capacity and stability of egg-white based foam systems, containing a fatty phase. It was determined that nonionic surfactants with low HLB increase foaming capacity and foam stability. The optimal ratio GMS: white was defined, which is 1:12,5. Surfactants with low HLB and presence of charge, namely anionic, amphoteric, lead to desorption of whites from the interphase surface aqueous solution-air that does not allow to obtain the system with the high foaming capacity and foam stability. It was established that reasonable concentration of DATEM and SSL in respect to providing high foaming capacity and stability of foam white systems, containing fat is the concentration up to 0.2 %. The obtained results allow to improve the air-nut semi-finished product technology by increasing stability due to introducing a certain surfactant concentration that allows to manufacture these products using industrial methods in catering establishments and confectionery shops.